Timing of atrazine application for control of quackgrass (Agropyron repens) - Gaynor, J.D.; Hamill, A.S. (Phytoprotection, 1993)
The use of foliar or soil applied atrazine to control quackgrass (Agropyron repens) in corn (Zea mays) was investigated. Atrazine treatments to control quackgrass significantly increased corn yield. Spring tillage without atrazine had little or no long term effect on quackgrass stand. A single application of 4.5 kg a.i. atrazine ha-1 applied in the fall or spring provided no better control of quackgrass than a split application of 2.25 kg a.i. atrazine ha-1 in either the foliage or bare soil experiments. Quackgrass recovery and soybean (Glycine max) yield were measured for 2 yr afterthe last atrazine application. Quackgrass did not recover to any significant extent within 2 yr after the cessation of the treatments on any of the atrazine treated plots. Atrazine residues from the previous fall applications significantly reduced soybean yield. Two years after the last atrazine treatment, soybean yields were similar, regardiess of former spring or fall atrazine application.